A Roadmap for More Renewable Energy - Harwood, William (Maine Policy Review, 2025)
In the Margaret Chase Smith Essay, William Harwood, former Maine Public Advocate, describes a roadmap for increasing renewable energy while keeping electricity costs affordable.